Assessing the Implications of Climate Change in Armenia: Challenges, Opportunities, and Policy Responses - Vardanyan, Tatevik («Տնտեսագետ» հրատ.)
Armenia, located in the South Caucasus, confronts significant challenges posed by climate change, including rising temperatures, altered precipitation patterns, and increased frequency of extreme weather events. However, amidst these challenges lie opportunities for proactive adaptation and mitigation efforts. Renewable energy development, ecosystem restoration, climate-smart agriculture, efficient water resource management, climateresilient infrastructure, community engagement, capacity building, and international collaboration present avenues for addressing climate change impacts effectively. By capitalizing on these opportunities and implementing targeted policy responses, Armenia can enhance its resilience, promote sustainable development, and mitigate the adverse effects of climate change. This paper assesses the implications of climate change in Armenia, delineates key challenges and opportunities, and outlines policy responses aimed at fostering climate resilience and sustainability.  Հարավային Կովկասում գտնվող Հայաստանը բախվում է կլիմայի փոփոխության հետևանքով առաջացած լուրջ մարտահրավերների, այդ թվում՝ ջերմաստիճանի բարձրացում, տեղումների մակարդակի փոփոխություն և եղանակային ծայրահեղ դրսևորումների հաճախականության աճ։ Մյուս կողմից՝ այս մարտահրավերների համար անհրաժեշտ է ստեղծել պրոակտիվ հարմարվողականության և մեղմացման ջանքերի հնարավորություններ: Վերականգնվող էներգիայի զարգացումը, էկոհամակարգերի վերականգնումը, կլիմայական համատեքստում «խելացի» գյուղատնտեսությունը, ջրի արդյունավետ կառավարումը, կլիմայի դիմացկուն ենթակառուցվածքները, համայնքի ներգրավվածությունը, կարողությունների զարգացումը և միջազգային համագործակցությունը հնարավորություն են տալիս արդյունավետորեն լուծելու կլիմայի փոփոխության ազդեցությունը: Армения, расположенная на Южном Кавказе, сталкивается с серьезными проблемами, вызванными изменением климата, включая повышение температуры, изменение режима осадков и увеличение частоты экстремальных погодных явлений. Однако среди этих проблем скрываются возможности для активной адаптации и усилий по смягчению последствий. Развитие возобновляемых источников энергии, восстановление экосистем, климатически оптимизированное сельское хозяйство, эффективное управление водными ресурсами, климатически устойчивая инфраструктура, вовлечение сообществ, наращивание потенциала и международное сотрудни-чество открывают возможности для эффективного решения последствий изменения климата.
Keywords: Natural Resource Economics And Environment